Heat stability of high-protein ultrafiltration retentate: Effect of concentration factor and stabilizing salts - Meena, Ganga Sahay; Singh, Ashish Kumar; Gupta, Vijay Kumar; Gujral, Harleen Kaur; Malhotra, Rashmeet Kaur (Indian Journal of Dairy Science, 2021)
Pasteurized cow skim milk (PCSM, 1×) was concentrated using ultrafiltration (UF) from 2 ×-7 × concentration factor (CF) to obtain retentates with different protein to total solids (TS) ratio. Alteration in chemical make-up led to poor thermal stability in UF retentates.  Therefore, this study was aimed to investigate the changes in permeate flux, chemical composition, pH, viscosity and heat coagulation time (HCT) of UF/DF retentates as a function of CF. Impact of high-shear (20,000 rpm/ 5 min), diafiltration (DF) with 150mM NaCl solution and stabilizing salts on HCT of high-protein 7×UF retentates were also evaluated. With increase in CF; TS, protein, fat, ash, calcium contents and viscosity increased significantly (p